Effect of Metabolic Stress to High-Load Exercise on Muscle Damage, Inflammatory and Hormonal Responses - Séverine Stragier; Jacques Duchateau; Frédéric Cotton; Julie Smet; Fleur Wolff; Jérémy Tresnie; Alain Carpentier (Sports)
To assess the impact of metabolic stress on blood lactate, muscle damage, inflammatory and hormonal responses following a high-load (70% maximum) strength training session, we compared two methods with a similar number of repetitions but that differed by their metabolic demand: the 3/7 method consisting in two series of five sets of an increasing number of repetitions (3 to 7) with a short inter-set interval (15 s) and the 8 × 6 method that comprises eight sets of six repetitions with a longer inter-set interval (2.5 min). Blood concentrations in lactate, creatine kinase (CK), myoglobin (MB), interleukine-6 (IL-6), leukocytes, growth hormone (GH), insulin-like growth factor-1 (IGF-1) and cortisol were determined before and after each session. Lactate concentration increased more (11.9 vs. 3.1 mmol/L; p < 0.001) for the 3/7 method whereas CK and MB concentrations were augmented similarly (p > 0.05) for both methods. Inflammatory markers (leukocytes and IL-6) increased (p < 0.01) more after the 3/7 method. GH and cortisol concentrations also increased more (p < 0.001) after the 3/7 method with no difference in IGF-1 concentrations between methods. Positive associations were found between the change in lactate and changes in IL-6 (r2 = 0.47; p < 0.01), GH (r2 = 0.58; p < 0.001) and cortisol (r2 = 0.61; p < 0.001) concentrations. In conclusion, the greater lactate accumulation induced by short inter-set intervals during a high-load training session is associated with enhanced inflammatory and hormonal responses, suggesting that metabolic stress might contribute to the greater adaptative response previously observed with this method.